2020
DOI: 10.1126/sciadv.aay1422
|View full text |Cite
|
Sign up to set email alerts
|

3D bioprinting dual-factor releasing and gradient-structured constructs ready to implant for anisotropic cartilage regeneration

Abstract: Cartilage injury is extremely common and leads to joint dysfunction. Existing joint prostheses do not remodel with host joint tissue. However, developing large-scale biomimetic anisotropic constructs mimicking native cartilage with structural integrity is challenging. In the present study, we describe anisotropic cartilage regeneration by three-dimensional (3D) bioprinting dual-factor releasing and gradient-structured constructs. Dual-factor releasing mesenchymal stem cell (MSC)–laden hydrogels were used for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
142
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(143 citation statements)
references
References 19 publications
1
142
0
Order By: Relevance
“…In fact, the composite scaffold demonstrated accelerated bone defect healing with higher levels of vessel invasion and less heterotopic bone formation if compared with implants homogeneously loaded with the same total amount of growth factors. Similar hydrogel-PCL composite scaffold strategies were proposed by the group of Sun et al (2020a , b , 2021) to generate living anisotropic cartilaginous tissues ( Figure 2 ). In the case of meniscus, PCL was molten to fabricate the physically supporting structure for the scaffold, choosing needle diameter, layer thickness, and fiber spacing of 200, 200, and 350 μm, respectively.…”
Section: Bioprinting Of Bioactive Hybrid Scaffolds For Musculoskeletal Tissuesmentioning
confidence: 71%
See 1 more Smart Citation
“…In fact, the composite scaffold demonstrated accelerated bone defect healing with higher levels of vessel invasion and less heterotopic bone formation if compared with implants homogeneously loaded with the same total amount of growth factors. Similar hydrogel-PCL composite scaffold strategies were proposed by the group of Sun et al (2020a , b , 2021) to generate living anisotropic cartilaginous tissues ( Figure 2 ). In the case of meniscus, PCL was molten to fabricate the physically supporting structure for the scaffold, choosing needle diameter, layer thickness, and fiber spacing of 200, 200, and 350 μm, respectively.…”
Section: Bioprinting Of Bioactive Hybrid Scaffolds For Musculoskeletal Tissuesmentioning
confidence: 71%
“…In particular, to chemically simulate the anisotropic phenotypes in native meniscus, microcarriers carrying CTGF were positioned in the outer one-third region, while those carrying TGF-β3 were used for the inner two-thirds regions of the meniscus construct. In vivo implantation into sheep showed that the ECM composition of the 3D-bioprinted constructs shared many characteristics of native meniscus, including the heterogeneous zonal expression of types I, II collagen and therewith the conferred anisotropic zonal function properties ( Sun et al, 2020a ). Dual-factor releasing and gradient-structured bioprinted constructs were also used for anisotropic cartilage regeneration ( Sun et al, 2020b ).…”
Section: Bioprinting Of Bioactive Hybrid Scaffolds For Musculoskeletal Tissuesmentioning
confidence: 99%
“…Biochemical gradients in tumor tissues greatly impact cellular processes such as cell adhesion, cell migration, cell proliferation, differentiation and angiogenesis. To provide a chemical gradient to simulate the proper maturation of bioprinted construct, multiple active agents can be loaded as multiple layers with varying layer spacing [114] .…”
Section: An Overview Of 3d Bioprintingmentioning
confidence: 99%
“…More recently, Sun et al. [ 71 ] developed a dual-factor (BMP4 and TGFβ3) releasing gradient structured human and rabbit cartilage construct using mesenchymal stem cells (MSC) and poly (lactic-co-glycolic acid) (PLGA) resulting in good interconnectivity. Overall, bioprinting of bone and cartilage tissue can provide a potential alternative to xenogeneic or allogeneic bone grafts.…”
Section: Applications Of 3d Bioprinting In Tissue Engineering and Biomedicinementioning
confidence: 99%